Flavonoids targeting of IκB phosphorylation abrogates carcinogen-induced MMP-9 and COX-2 expression in human brain endothelial cells - Tahanian E; Sanchez LA; Shiao TC; Roy R; Annabi B (Dove Medical Press, 2011)
Elizabeth Tahanian¹, Luis Arguello Sanchez¹, Tze Chieh Shiao², René Roy², Borhane Annabi¹¹Centre de Recherche BioMED, ²Centre de Recherche PharmaQAM, Département de chimie, Université du Québec à Montréal, QC, CanadaAbstract: Brain endothelial cells play an essential role as structural and functional components of the blood–brain barrier (BBB). Increased BBB breakdown and brain injury are associated with neuroinflammation and are thought to trigger mechanisms involving matrix metalloproteinase upregulation. Emerging evidence also indicates that cyclooxygenase (COX) inhibition limits BBB disruption, but the mechanisms linking metalloproteinase to COX remain unknown. In this study, we sought to investigate the nuclear factor-kappa B (NF-κB) signaling pathway, a common pathway in both the regulation of matrix metalloproteinase-9 (MMP-9) and COX-2 expression, and the inhibitory properties of several chemopreventive flavonoids. Human brain microvascular endothelial cells were treated with a combination of phorbol 12-myristate 13-acetate (PMA), a carcinogen documented to increase MMP-9 and COX-2 through NF-κB, and several naturally occurring flavonoids. Among the molecules tested, we found that fisetin, apigenin, and luteolin specifically and dose-dependently antagonized PMA-induced COX-2 and MMP-9 gene and protein expressions as assessed by qRT-PCR, immunoblotting, and zymography respectively. We further demonstrate that flavonoids impact on IκK-mediated phosphorylation activity as demonstrated by the inhibition of PMA-induced IκB phosphorylation levels. Our results suggest that BBB disruption during neuroinflammation could be pharmacologically reduced by a specific class of flavonoids acting as NF-κB signal transduction inhibitors.Keywords: blood–brain barrier, flavonoids, neuroinflammation, NF-κB signal transduction inhibitors